Implementasi Algoritme Poly1305-AES pada Protokol MQTT - Tista Pamungkas Ragil Alit; Ari Kusyanti; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Message Queuing Transport Telemetry (MQTT) is one of the Internet of Things (IoT) protocols specifically designed for communication between machines that have characteristics that can be used at low power, uses small bandwidth, connectivity in packet delivery and protocols using this technology to publish- subscribe. The MQTT protocol only provides authentication security for security which defaults do not guarantee the security of data in transmission so that data privacy and data integrity are problems in the implementation of the protocol. Therefore, the application of the Message Authentication Code (MAC) method uses the Poly1305-AES algorithm based on block ciphers. Based on testing, the Poly1305-AES algorithm has an increase in memory usage of 0.013MB to publishers and 0.028MB to customers and the Poly1305-AES algorithm can support changes, insertions and substitution data. This study presents the results of the Poly1305-AES algorithm which has a pretty good performance based on the value of increasing memory usage and resistance to attacks.